Novel primary thymic defect with T lymphocytes expressing gamma delta T cell receptor. Issue 7 (July 1989) - Geisler, C; Pallesen, G; Platz, P; Odum, N; Dickmeiss, E; Ryder, L P; Svejgaard, A; Plesner, T; Larsen, J K; Koch, C
Abstract : Flow cytometric analysis of the peripheral blood mononuclear cells in a six year old girl with a primary cellular immune deficiency showed a normal fraction of CD3 positive T cells. Most (70%) of the CD3 positive cells, however, expressed the gamma delta and not the alpha beta T cell receptor. Immunoprecipitation and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that most of the gamma delta T cell receptors existed as disulphide-linked heterodimers. Proliferative responses to mitogens were severely reduced, but specific antibody responses after vaccination could be detected. A thymic biopsy specimen showed severe abnormalities of both the thymic lymphoid and epithelial component with abortive medullary differentiation and almost an entire lack of Hassall's corpuscles. This patient represents a case of primary immune deficiency syndrome not previously described. Thymic deficiency associated with a high proportion of T cells expressing the gamma delta T cell receptor has been described in nude mice, and it is suggested that the immune deficiency of this patient may represent a human analogue.